2013
DOI: 10.1021/jo400090w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fully Substituted Pyrimidines

Abstract: ABSTRACT:A novel approach to the synthesis of fully substituted pyrimidine derivatives armed with an oxy-functionalized acetate chain at the ring is described. The manifold uses amidines as the nitrogen source and activated skipped diynes as the electrophilic reactive partners in a coupled domino strategy.In the first domino reaction, two consecutive aza-Michael additions assemble the 6-membered ring heterocycle while in the second domino process, a [H]-shift and a [3,3]-sigmatropic-rearrangement lead to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Preliminary data indicated that all the tested analogs displayed stronger inhibitory effects versus COX-2 enzyme (IC 50 ¼ 0.56-5.89 mM) than COX-1 enzyme (IC 50 ¼ 3.97-10.11 mM). SAR study revealed that the derivatives carrying a pyrazolyl scaffold in a hybrid conguration with the pyrazolo [3,4-d]pyrimidine moiety (64)(65)(66)(67)(68)(69) were typically stronger inhibitors of COX-2 enzyme than the compounds having other scaffolds. Moreover, the six hybrids were also noticed to be more COX-2 selective.…”
Section: Cyclooxygenase Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary data indicated that all the tested analogs displayed stronger inhibitory effects versus COX-2 enzyme (IC 50 ¼ 0.56-5.89 mM) than COX-1 enzyme (IC 50 ¼ 3.97-10.11 mM). SAR study revealed that the derivatives carrying a pyrazolyl scaffold in a hybrid conguration with the pyrazolo [3,4-d]pyrimidine moiety (64)(65)(66)(67)(68)(69) were typically stronger inhibitors of COX-2 enzyme than the compounds having other scaffolds. Moreover, the six hybrids were also noticed to be more COX-2 selective.…”
Section: Cyclooxygenase Inhibitionmentioning
confidence: 99%
“…The 4,5-dimethylpyrazole analog (69) was observed to be the strongest COX-2 inhibitor (IC 50 ¼ 0.56 mM), whereas the 5-aminopyrazole analog Scheme 24 Synthesis of pyrazolo[l,5-a]pyrimidin-7-ones (57a-q). Moreover, all the six analogs containing pyrazolyl moiety (64)(65)(66)(67)(68)(69) and the acetohydrazide analog ( 70) exhibited noteworthy anti-inammatory effects (ED 50 ¼ 87.9-10.1 mmol kg À1 ). The 5aminopyrazole analog ( 66) was noticed to be stronger (ED 50 ¼ 87.9 mmol kg À1 ) anti-inammatory agent than reference drug celecoxib (ED 50 ¼ 91.9 mmol kg À1 ).…”
Section: Cyclooxygenase Inhibitionmentioning
confidence: 99%
“…A considerable attention has been focused on synthesis of various substituted pyrimidines due to their interesting biological activities. [1][2][3] Aminopyrimidines constitute one of the important classes of pyrimidines. The pharmaceutical importance of these compounds lies on the fact that they can be effectively used as analgesics, anti-inflammatory, anticonvulsant, insecticidal, herbicidal, antitubercular, anticancer and antidiabetic agents.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Also, the pyrimidine and aminopyrimidine structures are frequently-occurring motifs in commercially available drugs such as anti-atherosclerotic aronixil, 7 anti-anxiolytic buspirone, 8 and other medicinally relevant compounds. 9,10 Symmetrical (1E,4E)-1,5-diarylpenta-1,4-dien-3ones (1) and their unsymmetrical analogues (2), which could be constructed easily, also possess structural features similar to α,α'bis(arylmethylene)cycloalkanones previously utilized by us for studying their reaction with thiourea and guanidine hydrochloride. 11,12 It is evident from the literature that the reaction of (1E,4E)-1,5diarylpenta-1,4-dien-3-ones (1 and 2) with guanidine has not been studied so far, although there are reports of cyclocondensation of varieties of α,β-unsaturated ketones with guanidine.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several marine alkaloids made up of pyrimidine rings also exhibit interesting biological activities . Therefore, due to a wide range of pharmaceutical applications, synthesis of pyrimidines has gained considerable attention in recent years . Substituted pyrimidines are an integral part of a variety of natural products .…”
Section: Introductionmentioning
confidence: 99%